(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In this article, the manifestations of ethnocultural syncretic processes and views on inculturation in it are revealed in a scientific-analytical, scientific-discussive way. In this, the features, important signs and social significance of ethnocultural syncretic processes are expressed in a scientific-analytical way. It is also pointed out that syncretic phenomena of ethnos sometimes occur as inculturation.